Evaluating Operational Risk in Environmental Modeling: Assessment of Reliability and Sharpness for Ensemble Selection - Pokorny, Scott; Stadnyk, Tricia A.; Ali, Genevieve (Journal of Hydrologic Engineering, 2023)

The 2011 flood event in the Assiniboine River Basin: causes, assessment and damages - Blais, Eric-Lorne; Greshuk, Jeremy; Stadnyk, Tricia (Canadian Water Resources Journal / Revue canadienne des ressources hydriques, 2016)

Identification of a preferred statistical distribution for at-site flood frequency analysis in Canada - Zhang, Ziyang; Stadnyk, Tricia A.; Burn, Donald H. (2020)
AbstractFloods are the most frequent natural disaster in Canada, putting Canadian lives and property at risk. Projected variations in precipitation and temperature are expected to further intensify...

An overview of river flood forecasting procedures in Canadian watersheds - Zahmatkesh, Zahra; Kumar Jha, Sanjeev; Coulibaly, Paulin; Stadnyk, Tricia (Canadian Water Resources Journal / Revue canadienne des ressources hydriques, 2019)
Keywords: Ouvrage_Collectif_Numéro1

Recent trends and variability in river discharge across northern Canada - Déry, Stephen J.; Stadnyk, Tricia A.; MacDonald, Matthew K.; Gauli-Sharma, Bunu (Hydrology and Earth System Sciences, 2016)
Abstract. This study presents an analysis of the observed inter-annual variability and inter-decadal trends in river discharge across northern Canada for 1964–2013. The 42 rivers chosen for this study span a combined gauged area of 5.26×106km2 and are selected based on data availability and quality, gauged area and record length. Inter-annual variability in river discharge is greatest for the eastern Arctic Ocean (coefficient of variation, CV=16%) due to the Caniapiscau River diversion into the La Grande Riviere system for enhanced hydropower production. Variability is lowest for the study area as a whole (CV=7%). Based on the Mann–Kendall test (MKT), no significant (p>0.05) trend in annual discharge from 1964 to 2013 is observed in the Bering Sea, western Arctic Ocean, western Hudson and James Bay, and Labrador Sea; for northern Canada as a whole, however, a statistically significant (p

Flow alteration impacts on Hudson Bay river discharge - Déry, Stephen J.; Stadnyk, Tricia A.; MacDonald, Matthew K.; Koenig, Kristina A.; Guay, Catherine (Hydrological Processes, 2018)

Hydrological modeling of freshwater discharge into Hudson Bay using HYPE - Stadnyk, Tricia A.; MacDonald, Matthew K.; Tefs, Andrew; Déry, Stephen J.; Koenig, Kristina A.; Gustafsson, David; Isberg, Kristina; Arheimer, Berit (2020)
This study details the enhancement and calibration of the Arctic implementation of the HYdrological Predictions for the Environment (HYPE) hydrological model established for the BaySys group of projects to produce freshwater discharge scenarios for the Hudson Bay Drainage Basin (HBDB). The challenge in producing estimates of freshwater discharge for the HBDB is that it spans over a third of Canada’s continental landmass and is 40% ungauged. Scenarios for BaySys require the separation between human and climate interactions, specifically the separation of regulated river discharge from a natural, climate-driven response. We present three key improvements to the modelling system required to support the identification of natural from anthropogenic impacts: representation of prairie disconnected landscapes (i.e., non-contributing areas), a method to generalize lake storage-discharge parameters across large regions, and frozen soil modifications. Additionally, a unique approach to account for irregular hydrometric gauge density across the basins during model calibration is presented that avoids overfitting parameters to the densely gauged southern regions. We summarize our methodologies used to facilitate improved separation of human and climate driven impacts to streamflow within the basin and outline the baseline discharge simulations used for the BaySys group of projects. Challenges remain for modeling the most northern reaches of the basin, and in the lake-dominated watersheds. The techniques presented in this work, particularly the lake and flow signature clusters, may be applied to other high latitude, ungauged Arctic basins. Discharge simulations are subsequently used as input data for oceanographic, biogeochemical, and ecosystem studies across the HBDB.